Application of the VDI 2221 method in the design of an air-to-water converter device - Salvatore Johanes Rega; Triwahyudin Rohman; Naufal Waliy Ishlah; Subekti Subekti (JTTM : Jurnal Terapan Teknik Mesin, 2024)
Indonesia's drought and water crisis problems have grown significantly in importance in recent years, especially in light of the country's fast population expansion, urbanization, and growing awareness of the effects of climate change. By 2040, there may be a clean water crisis in every region along Java's north coast, from Banten to Surabaya, according to projections made by the Indonesian Institute of Sciences (LIPI). The water crisis could be a major worldwide concern and will be a highly complicated issue. One approach to resolving the water shortage is to design an air-to-water converter device. The purpose of this research is to design a device that can efficiently and effectively convert air into water through condensation processes. The design will be based on the VDI 2221 Method. The rationale behind selecting the VDI 2221 Method is that it is a methodical approach to design that can help a designer generate and guide multiple design options. The primary mechanism of this apparatus is condensation, which turns air into dew points. The author utilized Solidworks 2020 to create the air-to-water conversion device. Through the stages of VDI 2221, the finest design outcomes were obtained from this design. The air-to-water converter mechanism in this design is constructed by version 2, which was chosen as the best option. Based on ASTM A36 material, theoretical calculations on the frame produced a safety factor of 1.45 and a maximum stress of 1.72414 × 108 N/m2. Based on the turbine shaft calculation, the maximum stress of 1.07235 × 108 N/m2 and the safety factor of 2.57379 were obtained using Aluminum 6061 material